A Study on the Development of a Web Based Urban Transit Reliability Evaluation System - Bae, Chul-Ho; Chu, Yul; Kim, Hyun-Jun; Koo, Tae-Yun; Lee, Ho-Yong; Suh, Myung-Won (Journal of mechanical science and technology, 2007)
Over the past twenty years, the maintenance system developed, and its importance increased. For the effective maintenance, the maintenance system has been developed by introducing the concept of RCM (Reliability Centered Maintenance). This research is to develop an effective maintenance system for urban transit based on the concept of RCM. RCM is a systematic approach to develop a cost-effective maintenance strategy based on the various components' reliability of the subject system. The final process of RCM determines appropriate failure maintenance strategies. For realization of RCM, reliability evaluation framework has been studied to compute the reliability index for urban transit. The framework requires the following processes: BOM (Bill of Materials), RBD (Reliability Block Diagram) based on FBD (Function Block Diagram), and failure code classification. The goal of this paper is to define the maintenance procedure for the subject system since successful maintenance system depends on an automated maintenance plan. This plan can be scheduled effectively by collecting and analyzing data from maintenance experience. For doing this, this paper proposes the web-based maintenance system for collecting data and the computing of MTBF (Mean Time between Failures) at the maintenance stage for analyzing data.[PUBLICATION ABSTRACT]